1934
DOI: 10.1029/tr015i002p00500
|View full text |Cite
|
Sign up to set email alerts
|

The choking of pore‐space in the soil and its relation to runoff and erosion

Abstract: The identification and evaluation of all factors influencing runoff and erosion on the erosive lands of the nation are manifestly studies of the most fundamental importance, especially in so far as they may be made to yield definite information upon methods of control over this insidious tendency upon cultivated lands. Investigations in progress at our Soil Erosion Experiment Stations have rather clearly shown that we may divide the factors that are mainly responsible for preventing or provoking erosion into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1941
1941
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The contribution of soil infiltration to annual SS yield treatment efficiencies is also important to note because Levine et al (2021) found infiltration rates in the ponding area to be lower than those outside the ponding area (Table 1). The results of this present study support previous findings that deposited sediments are able to clog soil pores and/or form a less permeable surface soil layer (Hendrickson, 1934;Reddi et al, 2000;Rice, 1974). Therefore, infiltration rates, and consequently SS yield treatment efficiencies, are likely to be highest in newly constructed DBs and will decrease over time and would likely decline faster in locations with higher erosion rates and greater SS loads deposited in DB ponding areas.…”
Section: Yields and Loadssupporting
confidence: 91%
“…The contribution of soil infiltration to annual SS yield treatment efficiencies is also important to note because Levine et al (2021) found infiltration rates in the ponding area to be lower than those outside the ponding area (Table 1). The results of this present study support previous findings that deposited sediments are able to clog soil pores and/or form a less permeable surface soil layer (Hendrickson, 1934;Reddi et al, 2000;Rice, 1974). Therefore, infiltration rates, and consequently SS yield treatment efficiencies, are likely to be highest in newly constructed DBs and will decrease over time and would likely decline faster in locations with higher erosion rates and greater SS loads deposited in DB ponding areas.…”
Section: Yields and Loadssupporting
confidence: 91%
“…Early investigators, particularly Wollny [13], called attention to the dispersive effects of rainfall on soil-structure. Lowder milk [14] and Hendrickson [15] confirmed Wollny's contention that the dispersion of the soil by rainfall resulted In the clogging of the soil-pores.…”
Section: Erosive Forces Of Surface-water Movementsmentioning
confidence: 80%
“…It is believed chemical soil stabilizers maintain aoil porosity during precipitation events by binding the soil particles together (Buxton et al 1979). On untreated soils, particles detached by rain drop impact and surface runoff fill pores, restrict infiltration, and cause surface runoff (Hendrickson) 1938). Increases in soil moisture will benefit germination and plant growth.…”
Section: Chemical Soil Stabilizersmentioning
confidence: 99%